Wiedza kursantów ośrodków szkolenia kierowców odnośnie użycia automatycznego defibrylatora zewnętrznego (AED) w trakcie akcji ratunkowej = Students knowledge of driver training center on the use an Automated External Defibrillator (AED) during rescue - Staniszewska, Anna; Korczak, Anna; Juszczyk, Grzegorz; Duda-Zalewska, Aneta; Olejniczak, Dominik; Dąbrowska-Bender, Marta; Bujalska-Zadrożny, Magdalena (Journal of Education, Health and Sport, 2015)
Staniszewska Anna, Korczak Anna, Juszczyk Grzegorz, Duda-Zalewska Aneta, Olejniczak Dominik, Dąbrowska-Bender Marta, Bujalska-Zadrożny Magdalena. Wiedza kursantów ośrodków szkolenia kierowców odnośnie użycia automatycznego defibrylatora zewnętrznego (AED) w trakcie akcji ratunkowej = Students knowledge of driver training center on the use an Automated External Defibrillator (AED) during rescue. Journal of Education, Health and Sport. 2015;5(5):67-75. ISSN 2391-8306. DOI: 10.5281/zenodo.17443 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A67-75 https://pbn.nauka.gov.pl/works/559145 http://dx.doi.org/10.5281/zenodo.17443 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Wiedza kursantów ośrodków szkolenia kierowców odnośnie użycia automatycznego defibrylatora zewnętrznego (AED) w trakcie akcji ratunkowej Students knowledge of driver training center on the use an Automated External Defibrillator (AED) during rescue Anna Staniszewska1*, Anna Korczak2, Grzegorz Juszczyk3, Aneta Duda-Zalewska3, Dominik Olejniczak3, Marta Dąbrowska-Bender3, Magdalena Bujalska-Zadrożny4 1 Katedra i Zakład Farmakologii Doświadczalnej i Klinicznej WUM 2 SPZOZ Warszawa Wawer 3 Zakład Zdrowia Publicznego WUM 4 Zakład Farmakodynamiki WUM *autor do korespondencji: dr n. med. Anna Staniszewska Katedra i Zakład Farmakologii Doświadczalnej i Klinicznej WUM Banacha 1b, 02-097 Warszawa, tel: (22) 116-61-60, e-mail: anna.staniszewska@wum.edu.pl Streszczenie Wstęp: Resuscytacja krążeniowo-oddechowa połączona z wczesną defibrylacją w ciągu 3-5 minut od utraty przytomności może dać efektywną reanimację w 49-75% przypadków, zaś każda minuta opóźnienia defibrylacji zmniejsza prawdopodobieństwo przeżycia poszkodowanego o 10-12%. Cel pracy: Praca miała na celu określenie stanu wiedzy przyszłych kierowców, jaką posiadają na temat automatycznych defibrylatorów zewnętrznych oraz ich użycia w trakcie akcji ratunkowej. Materiał i metoda: Badaniem objęto 200 osób, które wypełniły autorską ankietę na temat automatycznych defibrylatorów zewnętrznych. Badanie przeprowadzono na przełomie 2013 i 2014 roku. W badaniu wykorzystano metodę sondażu diagnostycznego, opartą na technice ankietowej z użyciem kwestionariusza ankiety stworzonej na potrzeby pracy. Do analizy j wyników posłużono się metodą statystyki opisowej. Wyniki i Wnioski: Na podstawie analizy odpowiedzi badanych na pytania ankiety stwierdzono, że wiedza kursantów na temat automatycznego defibrylatora zewnętrznego jest niedostateczna, zarówno pod względem znajomości działania AED, jak i jego lokalizacji. Wyniki przeprowadzonego badania wskazują na konieczność przygotowania i wdrożenia programu edukacyjnego na temat automatycznego defibrylatora zewnętrznego. Abstract Introduction: Resuscitation cardiopulmonary combined with early defibrillation within 3-5 minutes of unconsciousness can give effective resuscitation cardio-respiratory in 49-75% of cases and each minute of delay defibrillation reduces the probability of survival of the victim by 10-12%. Aim of the study. Evaluation of knowledge about Automated External Defibrillator among the driver training centers students. Material and methods. A group of 200 person was enrolled in order to evaluate the knowledge about Automated External Defibrillator by the special designed questionnaire. in late 2013 and 2014. The study used the method of diagnostic survey, questionnaire based on the technique of using a questionnaire survey of his own design. For the comparative analysis results are used by descriptive statistics. Results and conclusions. Results and conclusions. The knowledge about AED, among driver training centers students is inadequate. The results pointed at necessity of preparation and putting AED education program. Słowa kluczowe: wiedza, kursanci ośrodków szkolenia kierowców, automatyczny defibrylator zewnętrzny. Key words: knowledge, driver training centers students, Automated External Defibrillator.